INSPECTION STRATEGY DEVELOPMENT BASED ON RISK AND RELIABILITY EVALUATION OF OVERHEAD CATENARY SYSTEM - Rozzaq Prasetiyo, Edwin
Electric trains are one of the main modes of transportation in the Jabodetabek area, with the number of trips increasing every year, thus increasing the load on the overhead catenary system (OCS). Overhead catenary system is a vital system in the operation of KRL that functions to deliver electrical power from the traction substation to the KRL panthograph. Window time for inspection and maintenance is getting shorter, and the maintenance method used is still preventive and corrective based on time in accordance with PM 32 of 2011. This study aims to calculate the reliability, availability, and maintainability values of the critical components of the overhead catenary system, and propose an optimal inspection strategy based on risk analysis and RAM (Reliability, Availability, Maintainability) values. The methods used include a risk matrix to identify critical components, calculation of RAM values, and risk analysis using FMEA. The results showed that some critical components such as contact wire, messenger wire, and hanger had reliability values below the company's target, while other components met the target. The availability value of all critical components has met the target. FMEA analysis shows that the failure modes with the highest Risk Priority Number (RPN) values are feeder wire break, trolley wire break, messenger wire break, and pole break. The total cost of inspecting critical components increased by 10% compared to the existing inspection method.